Analysis of Reading Skills of Class III Students with Group Learning Method at Elementary School: Analisis Keterampilan Membaca Siswa Kelas III Dengan Metode Pembelajaran Kelompok di SD - Muhammad Albar; Ermawati Zulikhatin (Academia Open, 2022)
In learning Indonesian, each student has different abilities. One of the problems that elementary school (SD) students often encounter in their daily lives is problems related to not reading fluently. Because unwittingly fluent reading is often found in human activities in carrying out various activities in daily life, elementary school students are no exception. To describe the results of the third grade students reading skills with the group learning method at SDN Modong Tulangan, namely through the learning process students are expected to have the ability to think and interact to be able to solve problems in everyday life. Based on this, in this study the researchers used descriptive qualitative research with an approach to students. Qualitative research is research that produces descriptive data in the form of written and spoken words from people and behaviors observed in the field. The population in this study was 19 students divided into 9 female students and 10 male students in grade III at SDN Modong Tulangan. The instruments used are test questions, student response questionnaires, interviews, and observation sheets. The results showed that the application of group learning to reading skills was found in the teacher's teaching and learning activities which began by providing guidance to students through explanations from Indonesian books that made me smart, then students began to apply according to the explanations of the class teacher to use Indonesian books to make me smarter. Thorough and correct. The use of group learning can attract students' attention by encouraging students to learn to read which makes students' reading skills very good.